Acoustic enrichment can enhance fish community development on degraded coral reef habitat - Timothy A. C. Gordon (Nature Portfolio, 2019)
Healthy coral reefs have an acoustic signature known to be attractive to coral and fish larvae during settlement. Here the authors use playback experiments in the field to show that healthy reef sounds can increase recruitment of juvenile fishes to degraded coral reef habitat, suggesting that acoustic playback could be used as a reef management strategy.